2017
DOI: 10.21037/jss.2017.06.21
|View full text |Cite
|
Sign up to set email alerts
|

Single anterior cervical discectomy and fusion (ACDF) using self- locking stand-alone polyetheretherketone (PEEK) cage: evaluation of pain and health-related quality of life

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) constitutes the conventional treatment of cervical disc herniation due to degenerative disc disease (DDD). ACDF with plating presents a variety of complications postoperatively and stand-alone cages are thought to be a promising alternative. The aim of this study was firstly, to analyze prospectively collected data from a sample of patients treated with single ACDF using C-Plus self-locking stand-alone PEEK cage system, without the use of plates or scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Lu's research showed that in treating two level CSM, ACDF with stand-alone cage is associated with greater postoperative disc height and reduced chances of cervical lordosis 10 . Kapetanakis also proved that single level ACDF using stand-alone cage could significantly improve patients' life qualities 11 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lu's research showed that in treating two level CSM, ACDF with stand-alone cage is associated with greater postoperative disc height and reduced chances of cervical lordosis 10 . Kapetanakis also proved that single level ACDF using stand-alone cage could significantly improve patients' life qualities 11 .…”
Section: Discussionmentioning
confidence: 98%
“…The average JOA Scores of the AcAsa group 1 day, 6 months and 12months postoperatively were 12.57 ± 1.87 (6-16, 13), 13.10 ± 1.71 (8-16, 14) and 13.58 ± 1.69(8)(9)(10)(11)(12)(13)(14)(15)(16) 14). The corresponding improvement rates of JOA Score (RIS) were 21.63%±24.35% (-66.67%-75%, 25.00%), 30.14% ±24.31% (-66.67%-75%, 33.33%) and 39.68 ± 24.17 (-33.33%-83.33%, 42.86%).…”
mentioning
confidence: 98%
“…Despite the existence of numerous studies documenting QOL and functional outcomes after ACDF and a growing body of literature examining psychological scores in the context of lumbar spine surgery, there is considerably less evidence for the correlation between anxiety as well as depression and QOL outcomes after ACDF [13][14][15][16][17][18]39,[52][53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…One study defined fusion as the occurrence of anterior and posterior bone bridges on radiographs [21]. Park et al [24], Farrokhi et al [12], and Kapetanakis et al [22] defined fusion by the presence of motion and bone bridging on radiographs. Suess et al [18] defined fusion with three parameters consisting of bony bridging, absence of radiolucency at the implant-vertebrae interface, and the lack of motion on dynamic x-rays.…”
Section: Introductionmentioning
confidence: 99%
“…The subsidence rate was evaluated vaguely by radiographs in three studies [14,16,23]. Three studies defined subsidence as the radiographic change of at least 3 mm in the interbody space [13,17,24,25], whereas another two studies considered subsidence as a change of at least 2 mm in the interbody distance [21,22]. Kim et al [20] defined subsidence as a decrease of interbody height by more than 2.5 mm on lateral radiographs.…”
Section: Introductionmentioning
confidence: 99%